Case Report: Pseudoprogression With Nivolumab and Bevacizumab Followed by Recurrent Immune-Related Pneumonitis in Urothelial Carcinoma With Lung Metastasis - Yang, Zizhong; Zhang, Guoqing; Sun, Qiong; Liu, Minglu; Shao, Jiakang; Jiao, Shunchang (Frontiers in Oncology, 2021)
Background Combination therapy with immune checkpoint inhibitors (ICIs) and antiangiogenic agents is generally effective and well tolerated and might be effective for metastatic urothelial carcinoma (UC). However, ICI treatment is often associated with unique responses, such as pseudoprogression and ICI-related pneumonitis (CIP), which may influence clinical decision making and affect treatment. Although there have been many studies on the mechanism of pseudoprogression and CIP, the characteristics and relationship of these special events in a clinical setting remain rarely reported. Case Presentation Here, we present a patient with lung metastatic UC who underwent surgery and two lines of chemotherapy. The programmed cell death-1 (PD-1) inhibitor nivolumab and antiangiogenics agent bevacizumab were used as maintenance treatments. The patient experienced pseudoprogression after 2 PD-1 inhibitor cycles. The lesions in both lungs were enlarged on computed tomography (CT) imaging, and treatments were continued for another two cycles, after which the tumor size decreased to below baseline, followed by a durable response. However, after 4 months of pseudoprogression, the patient then developed CIP. The CIP was responsive to glucocorticoid therapy but recurred during ICI rechallenge, leading to the termination of immune therapy. Ultimately, the patient achieved durable, stable disease for over 18 months without further anticancer treatment. Conclusions Our case shows that pseudoprogression can occur in UC during immunotherapy even when combined with an effective antiangiogenic agent. In addition, pseudoprogression may be correlated with future adverse effects and a durable response. In the management of CIP, early rechallenge with ICIs may lead to CIP recurrence, which could be more severe and needs to be treated early and with appropriate drugs. Clinicians should be aware of atypical responses to ICIs and adjust the treatment plan accordingly.